Meningkatkan Hasil Belajar Siswa melalui Penerapan Pendekatan Keterampilan Proses Pada Pokok Bahasan Fungsi Organ Pernafasan Manusia di Kelas V - Nur Rahmatan Mursalin; Husnul Khotimah Rustam (Tunas Nusantara, 2022)
Sometimes students do not understand the lessons at school because they do not understand and the learning process is monotonous. Students to know the lesson including the function of human respiratory organs in grade V students. However, this research is more interesting and fun by professional teachers. For this reason, research is closely related to student interaction. The purpose of this study was to improve student learning outcomes through the application of a process skills approach to the subject of the function of the human respiratory organ. This research is assisted by qualitative methods. In particular, this research was designed with the type of Classroom Action Research (CAR). The number of research samples was 14 students of class V. The results of this study showed that the results obtained in cycle 1 showed satisfactory results in accordance with the predetermined success criteria, namely 70% with the lowest score of 70. The results of the study changed the cycle 2 with the addition of a deeper understanding of the material so that student learning outcomes are more than 70. Students understand the material of the respiratory organs well, so that students are expected to be actively involved in other subjects so that the improvement also increases.